Fiction, possibility and impossibility : three kinds of mathematical fictions in Leibniz’s work - Esquisabel, Oscar M. (2021)
Fil: Esquisabel, Oscar M. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina